2002
DOI: 10.1124/mol.61.4.936
|View full text |Cite
|
Sign up to set email alerts
|

The Virally Encoded Fungal Toxin KP4 Specifically Blocks L-Type Voltage-Gated Calcium Channels

Abstract: KP4 is a virally encoded fungal toxin secreted by the P4 killer strain of Ustilago maydis. Previous studies demonstrated that this toxin inhibits growth of the target fungal cells by blocking calcium uptake rather than forming channels, as had been suggested previously. Unexpectedly, this toxin was also shown to inhibit voltage-gated calcium channel activity in mammalian cells. We used whole-cell patch-clamp techniques to further characterize this activity against mammalian cells. KP4 is shown to specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 53 publications
1
27
0
1
Order By: Relevance
“…The voltage-dependence of activation of Ca v 1.3 may be more negative than that of Ca v 1.2 when expressed in INS-1 cells. However, the V 1/2 inactivation of the Ca v 1.2 and Ca v 1.3 clones used in this study are virtually identical when measured in the same expression system (Bell et al, 2001;Gage et al, 2002 (Lemmens et al, 2001;Bruton et al, 2003 (Gopel et al, 1999) and models of glucose-stimulated [Ca 2ϩ ] i oscillation (Fridlyand et al, 2003) (Schulla et al, 2003). However, the predominant L-type VDCC in rat and human ␤ cells is Ca v 1.3 (Seino et al, 1992 (Ma et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…The voltage-dependence of activation of Ca v 1.3 may be more negative than that of Ca v 1.2 when expressed in INS-1 cells. However, the V 1/2 inactivation of the Ca v 1.2 and Ca v 1.3 clones used in this study are virtually identical when measured in the same expression system (Bell et al, 2001;Gage et al, 2002 (Lemmens et al, 2001;Bruton et al, 2003 (Gopel et al, 1999) and models of glucose-stimulated [Ca 2ϩ ] i oscillation (Fridlyand et al, 2003) (Schulla et al, 2003). However, the predominant L-type VDCC in rat and human ␤ cells is Ca v 1.3 (Seino et al, 1992 (Ma et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have concluded that various splice variants of Ca v 1.3 activate at more negative potentials than Ca v 1.2 (Koschak et al, 2001;Scholze et al, 2001;Xu and Lipscombe, 2001). However, the voltage dependence of activation for the Ca v 1.3 and Ca v 1.2 clones used in this study are virtually identical when measured in human embryonic kidney 293 cells (Bell et al, 2001;Gage et al, 2002). Furthermore, we have not observed any significant difference in the current-voltage relationship of the DHPi fraction of current between the Ca v 1.2/DHPi and Ca v 1.3/DHPi cell lines using conventional whole recordings (G. Liu and G. H. Hockerman, unpublished observations).…”
Section: Intracellular Ii-iii Loop Of Ca V 13 Plays a Criticalmentioning
confidence: 99%
“…It has been demonstrated previously that KP4 inhibits Ca 21 uptake in fungal cells (Gage et al, 2001). Rather unexpectedly, KP4 was found to specifically block the L-type voltage-gated Ca 21 channels in a weakly voltage-dependent fashion (Gu et al, 1995;Gage et al, 2002). Since the antifungal activity of MsDef1 closely parallels that of KP4, we tested MsDef1 for its ability to block a Ca 21 channel in mammalian cells.…”
mentioning
confidence: 99%
“…Since the antifungal activity of MsDef1 closely parallels that of KP4, we tested MsDef1 for its ability to block a Ca 21 channel in mammalian cells. (Snutch et al, 1991), and Ca v 2.3 (Soong et al, 1993) from rat brain coexpressed with auxiliary subunits b 1b (Pragnell et al, 1991) and a 2 d (Ellis et al, 1988) in tsA-201 cells, was assayed as described previously (Gage et al, 2002). As shown in Figure 6A, 10 mM MsDef1 blocks approximately 90% of the Ca 21 current through the Ca v 1.2 (L-type) channel, with the maximum inhibition occurring after exposing the cells to the defensin for approximately 13 min.…”
mentioning
confidence: 99%